2012
DOI: 10.1371/journal.pone.0052570
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in the Global DNA Methylation Profile of Leukocytes Are Linked to Nutrition but Are Not Associated with the MTHFR C677T Genotype or to Functional Capacities

Abstract: Global DNA methylation of peripheral blood leukocytes has been recently proposed as a potential biomarker for disease risk. However, the amplitude of the changes in DNA methylation associated with normal aging and the impacts of environmental changes on this variation are still unclear. In this context, we evaluated the association of global DNA methylation with nutritional habits, tobacco smoking, body mass index (BMI), clinical laboratory parameters, polymorphism C677T MTHFR, functional cognition and the dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 55 publications
3
30
2
Order By: Relevance
“…Hypermethylation of MGMT genes has present a significantly interaction with polymorphisms of MTHFR C677T. The relationship between DNA methylation of P16, MGMT, hMLH1 and hMLH2 genes and MTHFR polymorphisms with the cancer risk has been pointed in several studies (Chen et al, 2012;Cheng et al, 2012;de Cássia Carvalho Barbosa et al, 2012;Gomes et al, 2012). The results of our study are associated with previous results.…”
Section: Discussionsupporting
confidence: 88%
“…Hypermethylation of MGMT genes has present a significantly interaction with polymorphisms of MTHFR C677T. The relationship between DNA methylation of P16, MGMT, hMLH1 and hMLH2 genes and MTHFR polymorphisms with the cancer risk has been pointed in several studies (Chen et al, 2012;Cheng et al, 2012;de Cássia Carvalho Barbosa et al, 2012;Gomes et al, 2012). The results of our study are associated with previous results.…”
Section: Discussionsupporting
confidence: 88%
“…If the methylome is indeed dynamic throughout life, then differences in DNA methylation profiles in identical twins should increase through life. As expected, studies demonstrate that although within-pair discordances are present from birth, 36 they increase with age, [37][38][39][40][41][42][43][44][45] particularly when twins experience divergent medical histories/ environments. [46][47][48][49] In fact, Novakovic and colleagues 50 found differences during gestation, which increased with gestational age.…”
Section: Introductionsupporting
confidence: 61%
“…Changes in the activity of folate metabolic enzymes induced by genetic polymorphisms may affect the methylation status of these genes and induce carcinogenesis (Chen et al, 2012;Gao et al, 2013 hMLH1 genes and cancer risk has been demonstrated in several studies (Chen et al, 2012;Gomes et al, 2012;Cheng et al, 2012;de Cássia Carvalho Barbosa et al, 2012). However, few studies have evaluated their association with gastric cancer risk.…”
Section: Discussionmentioning
confidence: 96%